Looking to the future building a curriculum for social activism - Hodson, Derek (SensePublishers, 2011)
In advocating an action-oriented and issues-based curriculum, this book takes the position that a major, but shamefully neglected, goal of science and technology education is to equip students with the knowledge, skills, attitudes and values to confront the complex and often ill-defined socioscientific issues they encounter in daily life as citizens in an increasingly technology-dominated world carefully, critically, confidently and responsibly. In outlining proposals for addressing socioscientific issues through a curriculum organized in terms of four increasingly sophisticated levels of consideration, the author adopts a highly critical and politicized stance towards the norms and values that underpin both scientific and technological development and contemporary scientific, engineering and medical practice, criticizes mainstream STS and STSE education for adopting a superficial, politically naïve and, hence, educationally ineffective approach to consideration of socioscientific issues, takes the view that environmental problems are social problems occasioned by the values that underpin the ways in which we choose to live, and urges teachers to encourage students to reach their own views through debate and argument about where they stand on major socioscientific issues, including the moral-ethical issues they often raise. More controversially, the author argues that if students are to become responsible and politically active citizens, the curriculum needs to provide opportunities for them to experience and learn from sociopolitical action. The relative merits of direct and indirect action are addressed, notions of learning about action, learning through action and learning from action are developed, and a case is made for compiling a user-friendly database reflecting on both successful and less successful action-oriented curriculum initiatives. Finally, the book considers some of the important teacher education issues raised by this radically new approach to teaching and learning science and technology. The book is intended primarily for teachers and student teachers of science, technology and environmental education, graduate students and researchers in education, teacher educators, curriculum developers and those responsible for educational policy. The author is Emeritus Professor of Science Education at the Ontario Institute for Studies in Education (University of Toronto), Adjunct Professor of Science Education at the University of Auckland and Visiting Professor of Science Education at the University of Hong Kong. His research interests include considerations in the history, philosophy and sociology of science and their implications for science and technology education, STSE education and the politicization of both students and teachers, science curriculum history, multicultural and antiracist education, and teacher education via action research. - Publisher's description.